2022
DOI: 10.3390/polym14224806
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin Hydrogels Incorporated with the Antioxidant Extract of Stryphnodendron adstringens Bark

Abstract: Barbatimão (Stryphnodendron adstringens) is a Brazilian medicinal plant known for its pharmacological properties, including healing activity related to its phenolic composition, which is chiefly given by tannins. In order to preserve its stability and bioactivity, barbatimão extracts can be incorporated into (bio-)polymeric matrixes, of which silk fibroin stands out due to its versatility and tunable properties. This work aimed to obtain barbatimão bark extract rich in phenolic compounds and evaluate its incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
1
4
0
1
Order By: Relevance
“…Frontiers in Drug Delivery frontiersin.org form hydrogels for SEM observation. These results supported those reported previously, confirming the incapacity of PG, VG, and PG-VG to form manually manipulable hydrogels (de Brito et al, 2022).…”
Section: Figuresupporting
confidence: 92%
“…Frontiers in Drug Delivery frontiersin.org form hydrogels for SEM observation. These results supported those reported previously, confirming the incapacity of PG, VG, and PG-VG to form manually manipulable hydrogels (de Brito et al, 2022).…”
Section: Figuresupporting
confidence: 92%
“…Scientific reports corroborate the strong wound-healing activity of S. adstringens [7][8][9][10][11] and experimental findings suggest its therapeutic effect on some chronic inflammatory or infectious conditions [12][13][14][15][16][17][18]. These results suggested that S. adstringens had a relevant anti-inflammatory role, involving its ability to modulate bone marrow macrophage polarization showing a reduction in interleukin 6 (IL-6) cytokines.…”
Section: Introductionmentioning
confidence: 67%
“…A espécie Stryphnodendron adstringens (Mart.) Coville (Fabales: Fabaceae), conhecida popularmente como barbatimão, devido a suas propriedades farmacológicas comprovadas cientificamente, é amplamente utilizada e estudada como planta medicinal em diversas regiões brasileiras (Freitas et al 2018;Ricardo et al 2018;Pereira Junior et al 2020;Brito et al 2022), especialmente em ensaios in vitro (Lima et al 2016;Baldivia et al 2018). A casca da árvore de S. adstringens é a principal parte utilizada para fins medicinais, seguida das folhas; o tronco é utilizado para fins madeireiros; a planta inteira tem valor ornamental; e aliado a isso, o barbatimão tem importância para indústria cosmética e na produção de corantes e de taninos (Lameira et al 2022).…”
Section: Artigo Full Open Accessunclassified